Small mammals as hosts of immature ixodid ticks - I.G. Horak; L.J. Fourie; L.E.O. Braack (Onderstepoort Journal of Veterinary Research, 2005)
Two hundred and twenty-five small mammals belonging to 16 species were examined for ticks in Free State, Mpumalanga and Limpopo Provinces, South Africa, and 18 ixodid tick species, of which two could only be identified to genus level, were recovered. Scrub hares, Lepus saxatilis, and Cape hares, Lepus capensis, harboured the largest number of tick species. In Free State Province Namaqua rock mice, Aethomys namaquensis, and four-striped grass mice, Rhabdomys pumilio, were good hosts of the immature stages of Haemaphysalis leachi and Rhipicephalus gertrudae, while in Mpumalanga and Limpopo Provinces red veld rats, Aethomys chrysophilus, Namaqua rock mice and Natal multimammate mice, Mastomys natalensis were good hosts of H. leachi and Rhipicephalus simus. Haemaphysalis leachi was the only tick recovered from animals in all three provinces.